1990
DOI: 10.3109/17453679008993062
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the patellar articulation with periosteal grafts: 4-year follow-up of 13 cases

Abstract: Reconstruction of the damaged articular surface of the patellar articulation with free periosteal grafts was performed in 13 patients who had not responded to previous treatment. After an average of 4 years, a good result was obtained in 8 patients and a fair result in 4 others. Only 1 patient, a 55-year-old man with severe patellar arthrosis, continued to have disabling pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(56 citation statements)
references
References 9 publications
0
51
0
5
Order By: Relevance
“…18,19 Nevertheless, we are still facing the essential problems of 20,21,22 and are feasible for biological resurfacing of articular cartilage defects. 23,24,25 In our work, we demonstrated that periosteal cells of the cambium layer of the proximal tibia, which seem to be most suitable according to Galley, 26 embedded in a specially manufactured fibrin matrix were able to repair full-thickness articular cartilage defects.…”
Section: Discussionmentioning
confidence: 85%
“…18,19 Nevertheless, we are still facing the essential problems of 20,21,22 and are feasible for biological resurfacing of articular cartilage defects. 23,24,25 In our work, we demonstrated that periosteal cells of the cambium layer of the proximal tibia, which seem to be most suitable according to Galley, 26 embedded in a specially manufactured fibrin matrix were able to repair full-thickness articular cartilage defects.…”
Section: Discussionmentioning
confidence: 85%
“…A few clinical studies have presented results of treatment of full-thickness cartilage defects in the knee joint by autologous periosteal transplantation [1,5,8,9,10,12], perichondrial transplantation [6], and autologous chondrocyte injection with a periosteal Abstract Twenty-six consecutive patients (19 men and 7 women) with a mean age of 31.5 years (range 19-52 years) who suffered from an isolated full-thickness cartilage defect of the patella (area ranged from 0.75 to 20.0 cm 2 ) and disabling knee pain were treated with autologous periosteal transplantation (without any chondrocytes). The duration of symptoms was 59 months (range 11-144 months).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies of repair enhancement of isolated chondral defects in patients (Engkvist and Johansson 1980, Sully et al 1980, Niederman et al 1985, Muckle and Minns 1989, Hoikka et al 1990, Homminga et al 1990, Jensen and Bach 1992, Bulstra et al 1993, Brittberg et al 1994a, 1994b, Lorentzon et al 1996 and usually the number of patients is small. Tippett (1996) and Johnson (1996) have reported the clinical outcome with use of Pridie drilling or abrasion chondroplasty with or without osteotomy for knee chondral defects.…”
Section: I N Ical Studiesmentioning
confidence: 99%